Analisis Normatif Penjatuhan Sanksi Etik dan Pidana pada Anggota Polri: Studi Kasus Ferdi Sambo - Pramudy, Deva Wira; Yusuf, Hudy (Media Hukum Indonesia (MHI), 2025)
Enforcement of discipline and ethics in the Indonesian National Police (Polri) institution is a fundamental aspect in maintaining professionalism and public trust. The police are also greatly needed by the Indonesian people and the international community. However, in some cases, Polri members who violate the law are often only subject to disciplinary or ethical sanctions without any criminal liability. The Indonesian National Police (Polri) institution has a strategic role in enforcing the law, maintaining security, and protecting the community. As law enforcement officers, Polri members are required to uphold the code of professional ethics and integrity in carrying out their duties. However, in practice, not a few Polri members are involved in criminal acts, thus giving rise to debate regarding the relationship between ethical disciplinary sanctions and criminal liability. This study aims to analyze whether the imposition of ethical disciplinary sanctions on Polri members who commit criminal acts can eliminate or drop their criminal liability in the legal system in Indonesia. This is in line with the principle of equality before the law, which emphasizes that every citizen has the same position in the eyes of the law. In some cases, there is inconsistency in the application of the law, where Polri members involved in criminal acts are treated differently compared to civilians. This paper also analyzes criminal acts and provides ethical sanctions to former members of the Indonesian National Police, namely, Mr. Ferdi Sambo. With the actions taken by FS, two violations occurred, namely, criminal violations and violations of the police code of ethics.